Colonialism, neo-colonialism, and anti-terrorism law in the Arab world / Fatemah Alzubairi. - Alzubairi, Fatemah, 1982- (Cambridge University Press, 2019)
The threat of personal harm and destruction from terrorist attacks is nowhere near as great as in Arab nations. However, are counter-terrorism laws in the Arab world formulated and enforced to protect or oppress? Colonialism, Neo-Colonialism, and Anti-Terrorism Law in the Arab World examines the relationship between Western influence and counter-terrorism law, focusing on the Arab world, which is, on the one hand, a hostile producer of terrorist organizations, and on the other, a leader in countering 'terrorism'. With case studies of Egypt and Tunisia, Alzubairi traces the colonial roots of the use of coercion and extra-legal measures to protect the ruling order, which are now justified in both the West and the Arab world in the name of counter-terrorism. Colonialism, Neo-Colonialism, and Anti-Terrorism Law in the Arab World provides important lessons for counter-terrorism, not just in these countries but also elsewhere in the world.